TINGKAT KEPUASAN PENGGUNA TERHADAP AKUN INSTAGRAM UMKM “OMAH BATIR” - Haikal Azril Hikmatyar; Ali Syah Al Banjari; Adrianus Angoro Susanto; Ahmad wahyu Kurniawan; Ito Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze user satisfaction with the Instagram account of the MSME Omah Batir as a digital marketing medium based on social media. The use of Instagram by MSMEs has become increasingly strategic along with changes in consumer behavior that rely on social media to seek information, evaluate products, and interact with business actors. This research employs a quantitative approach using descriptive statistical methods. Data were collected through an online questionnaire distributed to 51 respondents who are active followers of the Omah Batir Instagram account. User satisfaction was measured based on five main indicators: content quality, visual appeal, interaction, account manager responsiveness, and users’ intention to follow or loyalty. The results indicate that the majority of respondents provided positive evaluations across all examined indicators. Informative and consistent content, attractive visual presentation, and effective interaction and responsiveness from the account administrator were found to contribute significantly to user satisfaction. Furthermore, user loyalty was relatively high, as reflected in the willingness to continue following and recommending the account to others. These findings suggest that the management of the Omah Batir Instagram account has been effective and may serve as a reference for other MSMEs in developing user satisfaction–oriented digital marketing strategies.